2015
DOI: 10.1016/j.watres.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic degradation of antibiotics: Characterization and pathway analysis

Abstract: Antibacterial activity elimination a b s t r a c tAntibiotics in wastewaters must be degraded to eliminate their antibacterial activity before discharging into the environment. A cathode can provide continuous electrons for the degradation of refractory pollutants, however the cathodic degradation feasibility, efficiency and pathway for different kinds of antibiotics is poorly understood. Here, we investigated the degradation of four antibiotics, namely nitrofurazone (NFZ), metronidazole (MNZ), chloramphenicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(92 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…CV analysis preliminarily indicated that almost no reductive current was recorded for the enrichment within 72 h, which was quite close to the cyclic voltammogram of PBS control. In contrast, NFZ containing medium (50 mg/L) showed three obvious reduction peaks those were consistent with our previous study (Kong et al, 2015a). CV result indirectly showed the added NFZ could be efficiently reduced by the acclimated NFZ-reducing consortium (Fig.…”
Section: Nfz-reducing Consortium Capabilitysupporting
confidence: 92%
See 4 more Smart Citations
“…CV analysis preliminarily indicated that almost no reductive current was recorded for the enrichment within 72 h, which was quite close to the cyclic voltammogram of PBS control. In contrast, NFZ containing medium (50 mg/L) showed three obvious reduction peaks those were consistent with our previous study (Kong et al, 2015a). CV result indirectly showed the added NFZ could be efficiently reduced by the acclimated NFZ-reducing consortium (Fig.…”
Section: Nfz-reducing Consortium Capabilitysupporting
confidence: 92%
“…Though the degradation rate, efficiency and degree of NFZ were obviously affected by different cathode potentials, three mainly identified degradation products including AMH, AMN and NFF were consistent (Kong et al, 2015a). In this study, the three products of both the biocathode and open circuit biofilms were the same as previously identified based on the HPLC peak sequence and retention time.…”
Section: Formation Of Nfz Reduction Products Under Different Operatiosupporting
confidence: 73%
See 3 more Smart Citations